Cancer Therapy: Vaginal Delivery of Paclitaxel via Nanoparticles with Non‐Mucoadhesive Surfaces Suppresses Cervical Tumor Growth (Adv. Healthcare Mater. 7/2014). Issue 7 (10th July 2014) - Yang, Ming; Yu, Tao; Wang, Ying‐Ying; Lai, Samuel K.; Zeng, Qi; Miao, Bolong; Tang, Benjamin C.; Simons, Brian W.; Ensign, Laura M.; Liu, Guanshu; Chan, Kannie W.Y.; Juang, Chih‐Yin; et al.
<x xml:space="preserve">Abstract</x> Mucus‐penetrating particles (MPP) efficiently bypass the sticky mucus layer in the female reproductive tract, whereas conventional nanoparticles (CP) are trapped and rapidly cleared. On page 1044, J. Hanes and team show how MPP achieve close proximity to mouse cervical tumors and provide sustained release of chemodrugs, resulting in superior efficacy compared to CP. The MPP platform may hold similar promise for local chemotherapy against tumors at other mucosal surfaces. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>